Perancangan Inkubator Telur Puyuh Otomatis Berbasis IoT dengan Sistem Pemantauan Jarak Jauh Menggunakan Spreedsheat - Alvin Ardiniansyah; Reza Setiawan; Aa Santosa; Bhisma Mahendra (Universitas Muhammadiyah Metro, 2026)
The research method used was an experimental comparative approach by comparing the performance of an IoT-based automatic incubator with a conventional incubator. The automatic incubator utilized an ESP32 microcontroller, DHT22 temperature and humidity sensor, heating lamps, exhaust fan, and automatic egg turning system using a servo motor. Monitoring data were transmitted via internet connection for real-time observation with spreadsheet. Each incubator was tested using 30 quail eggs during an incubation period of 18 days.The results showed that the IoT-based incubator was able to maintain temperature stability within the range of 37.2°C–38.2°C and humidity between 60%–68%. Meanwhile, the conventional incubator experienced larger temperature fluctuations ranging from 35.4°C to 40.0°C. The automatic incubator achieved a hatchability rate of 90% with an average hatch weight of 8.9 g, while the conventional incubator only achieved 70% hatchability with an average hatch weight of 7.8 g. Based on the results, the IoT-based automatic incubator demonstrated better performance in maintaining incubation stability and improving hatchability efficiency compared to the conventional system. The implementation of IoT technology also enabled real-time monitoring and automatic control, making the incubation process more effective and efficient.